Electron radiation in the field of running linearly polarized electromagnetic waves - Grigor’ev, Yu.N.; Drebot, I.V.; Zvonaryova, O.D.; Zelinskiy, A.Yu. (Вопросы атомной науки и техники, 2005)
The results of integration of the Lorentz equation for a relativistic electron in the field of the sum of linearly
polarized electromagnetic waves with different frequencies running in the same direction are presented. It was shown
that electron velocity is almost periodic function of time when electron is moving in the field of running linearly
polarized electromagnetic waves. Expansion of the field radiated by the electron in the generalized Fourier series in
calculating the spectral-angular distribution of the radiation intensity was used. Expressions for frequency and
intensity of direct and back Compton radiation on the combinative harmonics of the external field were obtained. Наведено результати інтегрування рівняння Лоренца для релятивістського електрона в полі, яке уявляє собою суму бігучих в одному напряму лінійно поляризованих електромагнітних хвиль різної частоти. Показано, що під час руху електрона в полі бігучих лінійно поляризованих хвиль, швидкість електрона є майже періодичною функцією часу. При обчислюванні спектрально-кутового розподілення інтенсивності випромінювання використано розклад випромінюваного електроном поля в узагальнений ряд Фур’є. Отримано формули зворотного та прямого комптонівського випромінювання на комбінаційних гармоніках зовнішнього поля. Приведены результаты интегрирования уравнения Лоренца для релятивистского электрона в поле,
представляющем собой сумму бегущих в одном направлении линейно поляризованных электромагнитных
волн разной частоты. Показано, что при движении электрона в поле бегущих линейно поляризованных волн,
скорость электрона является почти периодической функцией времени. При вычислении спектрально-
углового распределения интенсивности излучения использовано разложение излученного электроном поля в
обобщенный ряд Фурье. Получены формулы обратного и прямого комптоновского излучения на
комбинационных гармониках внешнего поля.